PENGARUH KABUT GARAM TERHADAP KINERJA ISOLATOR 20 KV BERBAHAN POLIMER RESIN EPOXY - Sudirman S; Sri Kurniati A (Jurnal Media Elektro, 2012)
This paper aim to know polymer isolator performance of epoksi resin 20 kV in condition of salt fog and compared to cleanness fog. Measurement done in a cloud chamber (Chamber Test) which its the temperature is arranged to become 3 level: low (00 - 250C), medium (250 - 350C) and height (350- 450C). And then is done measurement of good blowby current in condition of clean fog and also salt fog by taking polymer isolator sample in condition of cleanness and pollutant. Result of study indicates that isolator performance hardly influenced by condition of area of especially residing in coast area that is often foggy salt. In condition of clean fog without pollutant is obtained by examination of leaky current 20 uA at temperature 400, while at condition of salt fog 25 uA. Finally, in condition of light pollutant of rising blowby current becomes 21 uA at condition of cleanness while at condition of salt fog becomes 26 uA.